1982
DOI: 10.1182/blood.v60.4.814.814
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and clinical effects of repeated blood exchange in familial erythrophagocytic lymphohistiocytosis

Abstract: Depressed cellular immune function and increased susceptibility to infection characterize familial erythrophagocytic lymphohistiocytosis (FEL), a usually fatal autosomal recessive disease. One component of the immunodeficiency is plasma-mediated inhibition of lymphocyte proliferation. We have tested whether repeated plasma or blood exchange would decrease plasma inhibitory activity and improve cellular immune function in FEL. Following this treatment, reduction in plasma inhibitory activity, reversal of depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The x 2 test value obtained (2.76) is compatible, although not conclusive, in this respect. Heterogeneity with respect to cellular immune dysfunction in FHL (Ladisch et al 1982;Stark et al 1987) is consistent with the possibility that multiple defects underlie the disease phenotype. Since the ethnic background of family 5 varied from that of the other families included in the study, it is conceivable that within individual populations defects of different genes predominate among FHL kindreds.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The x 2 test value obtained (2.76) is compatible, although not conclusive, in this respect. Heterogeneity with respect to cellular immune dysfunction in FHL (Ladisch et al 1982;Stark et al 1987) is consistent with the possibility that multiple defects underlie the disease phenotype. Since the ethnic background of family 5 varied from that of the other families included in the study, it is conceivable that within individual populations defects of different genes predominate among FHL kindreds.…”
Section: Discussionsupporting
confidence: 61%
“…immune defect in FHL is provided by evidence that allogeneic bone marrow transplantation may be curative in the presence of mixed chimerism, despite limited donor engraftment (Landman-Parker et al 1993) and the occurrence of hemophagocytic disorders secondary to Tlymphoproliferative disorders (Falini et al 1990). Selective deficiency in natural killer cell activity (Ladisch et al 1982;Perez et al 1984) and T-cell cytotoxicity (Arico et al 1988;Egeler et al 1996) is frequently observed, although its relation to the pathogenesis of FHL remains uncertain.…”
Section: Figurementioning
confidence: 99%
“…In addition to the primary immune defects seen with FHL, the exaggerated inflammatory response and hypercytokinemia contribute to the organ injury that may cause the rapid demise of the patient [9]. Repeated plasma exchange has been shown to produce clinical improvement in patients with FHL in whom the therapeutic benefit was attributed to the lowering of the putative plasma suppressor factor described by Ladisch et al [10]. Increasingly, cytokines and chemokines are being shown to cause many of the observed clinical and biochemical features of FHL.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide was first reported in 1980 as a treatment for HLH among 3 children (Ambruso et al 1980). Plasma exchange was later attempted with transient resolution of symptoms in few patients (Ladisch et al 1982). A combination therapy including etoposide, steroids, intrathecal methotrexate and cranial radiation therapy in 1985 revealed prolonged remission in patients with FHLH (Fischer et al 1985).…”
Section: Treatmentmentioning
confidence: 99%